2022
DOI: 10.3390/designs6050095
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3D-Printed Orthopedic Insoles for Patients with Diabetes and Evaluation with Electronic Pressure Sensors

Abstract: The correct distribution of loads on foot, known as plantar pressures, is a relevant parameter for evaluating the evolution of some diseases. Anomalies can lead to pain and discomfort in other body parts. Diabetes changes foot tissues and compromises biomechanics, resulting in ulcers and, eventually, amputation. Customized insoles allow the redistribution of plantar pressures and are a complementary strategy to diabetes management. Nowadays, scanning and 3D printing technology can generate faster and more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Foot insoles are used in relieving pains (especially site-specific pains) in persons hailing diabetic foot complications. Plantar pressures (or distribution of loads on foot) in diabetic patients act as one of the important parameters in evaluating the progression of diabetes ( Zuniga et al, 2022 ). Custom insoles, also referred to as “Standard of Care (SoC) insoles” are well-known for its use in dealing with diabetic foot plantar pressures.…”
Section: Applications Of 3d Printing and 3d Bioprinting In Diabetic P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Foot insoles are used in relieving pains (especially site-specific pains) in persons hailing diabetic foot complications. Plantar pressures (or distribution of loads on foot) in diabetic patients act as one of the important parameters in evaluating the progression of diabetes ( Zuniga et al, 2022 ). Custom insoles, also referred to as “Standard of Care (SoC) insoles” are well-known for its use in dealing with diabetic foot plantar pressures.…”
Section: Applications Of 3d Printing and 3d Bioprinting In Diabetic P...mentioning
confidence: 99%
“…In the past few days, integration of 3D printing, scanning, materials chemistry and software application have been highly beneficial in fine-tuning the procedure of insole fabrication process and in enhancing the performance of insoles as well ( Zuniga et al, 2022 ; Mancuso et al, 2023 ). For instance, Zuniga et al (2022) developed 3D-printed insoles employing the thermoplastic polyether-polyurethane and thermoplastic polyurethane polyester-based polymer for diabetic patients and evaluated its efficiency in plantar pressure distribution with electronic pressure sensors ( Zuniga et al, 2022 ). The insoles were found to perform well and were reported to possess potential in managing diabetes.…”
Section: Applications Of 3d Printing and 3d Bioprinting In Diabetic P...mentioning
confidence: 99%
“…The foot silhouette was sketched from the impression taken to generate the insole contour (Figure 6b). The 3D biomodel was placed right above the insole, using Boolean operations and working with surfaces to create a customized insole based on parametric designs set by specialized insole design software [44][45][46][47]. Working with surface modeling for the insole design allowed certain regions to be smoothed and the orthosis to be adjusted to foot morphology (Figure 6c).…”
Section: Second Case Studymentioning
confidence: 99%
“…Recent studies have investigated the effectiveness of 3D-printed insoles in managing foot ulcers, flat feet, high-arched feet, leg length discrepancies, and diabetic foot conditions. Zuñiga et al [16] demonstrated comparable pressure distribution between 3D-printed and standard insoles. Another research reported improved foot function and comfort with 3D-printed insoles in individuals with flat feet [17].…”
Section: Introductionmentioning
confidence: 96%